Pelaksanaan Pelayanan Publik Hak Tanggungan Terintegrasi Secara Elektronik Oleh Kantor Pertanahan Kota Jambi - Hariss, Abdul; Yanti, Herma; Fauzia, Nur; Haris, Bilqist (Universitas Batanghari Jambi, 2024)
The Ministry of Agrarian Affairs and Spatial Planning/National Land Agency has launched electronic land services. The electronic service in question is electronically integrated mortgage rights (HT-el). With land services through an electronic system that is easy to use, it is the aim of the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency to remain competitive in the digital era and help the community. The aim of this research is to determine the implementation, obstacles faced, and efforts made by the government in implementing electronic mortgage rights. The research method used is empirical juridical, through a socio-legal-research approach. The data sources used in this research are library data from laws, books, journals and the internet; Field data comes from interviews with related parties. Land office counters are no longer needed because HT-el services are all done online. This is a significant achievement of the Ministry of ATR/BPN in its efforts to improve the efficiency and quality of land services through implementing the e-Government concept. Based on the research findings, it can be concluded that the Jambi City Land Office has followed the process contained in the ATR/BPN Ministerial Regulation Number 5 of 2020 and HT-el technical instructions Number 2 of 2020 in implementing HT-el. Even though there are several obstacles, including system problems, inappropriate application files, unverified land parcel data, and SPS payments outside working hours, implementation continues.